Possible design of a management information system for the Research Management Center, University of the Philippines Los Baños - Lapastora, Lydia R.; Sison, Josephine C.; Anday, Vilma G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1988)
This study sought to explore what management information system (MIS) design can be implemented for the Research Management Center (RMC) of the College of Economics and Management, University of the Philippines Los Baños in general. Specifically, the study sought to find out the information requirements of RMC and the data elements and components of and MIS for the Center
The respondents of the study were researchers, faculty members and managers who are actual users of the library within the complex of the College of Economics and Management of the University of the Philippines Los Baños particularly with management background for the period of three years (1996 to 1998). The survey method with a structured questionnaire was used in this study to determine the structure and data elements to be included in the proposed MIS for RMC. A pre-tested questionnaire was utilized for gathering the required data. The questions included information on personal data such as age, educational attainment, field of specialization; the forms in which the information are made available such as the transaction documents on screen, user-machine dialogue results, preplanned inquiry responses, ad hoc reports and inquiry responses and the preplanned reports; information requirements such as the human resource development data, program and policies data, research and evaluation data, training and evaluation data and the physical infrastructure data components of each of an MIS needed for RM
The average age of the respondents is within the 31 to 40 years old range and having provided at least a year of service to the University. The respondents were also found to have undertaken graduate studies, which later supported their position in the academic community being professor and faculty servicing the College of Economics and Management. Their backgrounds were deemed to affect their knowledge of the information and information requirement in CEM particularly in RMC. The most needed information requirement identified were found to be frequently needed by the respondents. Respondents identified the formulation of policies and programs as the most needed information in their respective work. Correlation analysis showed that the socio-demographic characteristics such as age, educational attainment and the field of specialization have no significant association with their ratings on the need for the kind of informatio
The form in which information are made available by the respondents is the preplanned inquiry responses because the information is presented in its simplest forms and since the inquiry have been preplanned, the responses are received immediately by the use of the system. It was found that in the present time when technology and fast-paced activities become the trend, short but substantial information must be provided to its users. Likewise, respondents said that what they need are updated and substantial data that are easily made available for their use rather than their lengthy report
Based on the results of the study, it is recommended that the MIS design for the Center be developed for a better information management syste
Computer print out.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Management information system; University of the Philippines, Los Banos. Research Management Cente